2017
DOI: 10.1039/c7cc02251d
|View full text |Cite
|
Sign up to set email alerts
|

Ligand induced structural isomerism in phosphine coordinated gold clusters revealed by ion mobility mass spectrometry

Abstract: Structural isomerism in ligated gold clusters is revealed using electrospray ionization ion mobility spectrometry mass spectrometry. Phosphine ligated Au clusters are shown to adopt more extended type structures with increasing exchange of methyldiphenylphosphine (MePPh) for triphenylphosphine (PPh). These ligand-dependant structure-property relationships are critical to theoretical modeling of clusters as well as their applications in catalysis and photovoltaics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…Laskin et al reported structural changes in gold clusters induced by interactions between differently substituted phosphine ligands and gold cores. [15] Also, the Pradeep group reported the first observation of the presence of ligand induced isomers of glutathione protected Ag11 by IM-MS where two isomers can be distinguished by their different drift times. [16,17] Our group showed how IM MS studies can get insight into the size [18] of glutathioneprotected gold nanoclusters and can help in structural determination [19] in the case of inorganic nanoclusters.…”
Section: Thus This Complementary Technique Has Beenmentioning
confidence: 99%
“…Laskin et al reported structural changes in gold clusters induced by interactions between differently substituted phosphine ligands and gold cores. [15] Also, the Pradeep group reported the first observation of the presence of ligand induced isomers of glutathione protected Ag11 by IM-MS where two isomers can be distinguished by their different drift times. [16,17] Our group showed how IM MS studies can get insight into the size [18] of glutathioneprotected gold nanoclusters and can help in structural determination [19] in the case of inorganic nanoclusters.…”
Section: Thus This Complementary Technique Has Beenmentioning
confidence: 99%
“…For example, the structural changes upon ligand exchange from [Au8(PPh3)7] 2+ and [Au11(PPh3)9H] 2+ with methyldiphenylphosphine (MePPh2) were evidenced by IM-MS analysis. 206 Recently, Hirata et al studied the effect of collisional excitation on structural properties of nanoclusters and showed that phosphine-protected gold clusters undergo conversion to more compact isomers. 207 Very recently, Hakkinen and coworkers showed that IM-MS was a technique of choice to probe interconversion between isomers of Au25(SR)18 clusters.…”
Section: Ion Mobility-msmentioning
confidence: 99%
“…The challenge of identifying and resolving occluded species is non-trivial to the study of dynamic libraries of self-assembling species in solution ( Figure 3 ) ( Misuraca et al, 2014 ). Mass spectrometry gives ready access to real time analysis of dynamic systems on a millisecond timescale ( Schalley and Springer, 2009 ; Hudgens et al, 2011 ; Pettibone and Hudgens, 2012 ; Olivares et al, 2014 ; Yunker et al, 2014 ; Ligare et al, 2017a ; Ligare et al, 2017b ; Ujma et al, 2017 ; Schnell et al, 2019 ; Mehara and Roithová, 2020 ; Zelenka and Roithová, 2020 ). The difficulties of occluded isobaric and isomeric species can be overcome by adding a filter for shape and size, in addition to m/z , namely, an ion-mobility spectrometer (IMS) ( Ujma et al, 2017 ; Polewski et al, 2021 ).…”
Section: Self-assembly and Coordination Driven Self-assemblymentioning
confidence: 99%